SWOT ANALYSIS ON CASH WAQF FUNDRAISING STRATEGIES IN WAQAF-BASED EDUCATIONAL INSTITUTIONS - Ghazy Triyatno (Journal of Islamic Economics and Philanthropy, 2022)
Implementing an effective waqf fundraising strategy management is essential. Waqf funds are needed by guardians or mutawalli in order to manage them productively. However, it is not easy to raise funds because of the non-obligatory status of waqf unlike zakat. Especially in today's contemporary era, the challenges are getting tougher. Although historically waqf has played a significant role in easing the burden on people in need, however in current conditions it must be managed strategically. This study purposed to identify the impact of implementingwaqf fundraising strategies in tazakka waqf institutions and finding various alternative strategies to be recommended for further implementation. This type of research is a field research that using a qualitative approach with a triangulation model. Data collection was obtained from observations, interviews and documentation collection related to the current situation. in the strategy analysis of this research using SWOT analysis, the results showed that the tazakka waqf institution has applied the theory of fundraising strategy proposed by Sargeant which divides the fundraising strategy into four strategies, namely; Dialogue fundraising, corporate fundraising, multichannel fundraising, donor retention and development. As for the results of strategy analysis by using swot analysis, this study resulted in eight recommended strategies to be implemented by tazakka waqf institutions.  This study can be a reference for waqf fundraising strategies in waqf-based educational institutions or waqf institutions. This study provides consideration for waqf institutions in choosing waqf fundraising models to develop waqf institutions in achieving the goals, vision and mission of the institution.